A One‐Dimensional π–d Conjugated Coordination Polymer for Sodium Storage with Catalytic Activity in Negishi Coupling - Chen, Yuan; Tang, Mi; Wu, Yanchao; Su, Xiaozhi; Li, Xiang; Xu, Shuaifei; Zhuo, Shuming; Ma, Jing; Yuan, Daqiang; Wang, Chengliang; Hu, Wenping (Angewandte Chemie International Edition, 2019)
π‐d Conjugated coordination polymers (CCPs) have attracted much attention for various applications, although the chemical states and structures of many CCPs are still blurry. Now, a one‐dimensional (1D) π‐d conjugated coordination polymer for high performance sodium‐ion batteries is presented. The chemical states of the obtained coordination polymer are clearly revealed. The electrochemical process undergoes a three‐electron reaction and the structure transforms from C=N double bonds and NiII to C−N single bonds and NiI, respectively. Our unintentional experiments provided visual confirmation of NiI. The existence of NiI was further corroborated by its X‐ray absorption near‐edge structure (XANES) and its catalytic activity in Negishi cross‐coupling. A conjugated coordination polymer for sodium‐ion batteries is presented. The chemical states of the obtained coordination polymer are clearly revealed, indicating that the electrochemical process undergoes a three‐electron reaction and the structure transforms from C=N double bonds and NiII to C−N single bonds and NiI, respectively. Furthermore, the discharged electrodes (NiI) can be used as quasi‐single‐atom catalyst in Negishi cross‐coupling.